If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 76 = (2x + 4) Reorder the terms: 76 = (4 + 2x) Remove parenthesis around (4 + 2x) 76 = 4 + 2x Solving 76 = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 76 + -2x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 76 + -2x = 4 + 0 76 + -2x = 4 Add '-76' to each side of the equation. 76 + -76 + -2x = 4 + -76 Combine like terms: 76 + -76 = 0 0 + -2x = 4 + -76 -2x = 4 + -76 Combine like terms: 4 + -76 = -72 -2x = -72 Divide each side by '-2'. x = 36 Simplifying x = 36
| 6x=4(x-9) | | 16a-10a-2a= | | 3a+5b=20 | | 4x+10=-28 | | -5m+3(m-5)=-(2n+15) | | 8h-1=8h+4 | | 2(w-2)+7=3-4w | | 0.5(220-a)=99 | | X+42+x=180 | | M+.3=3m+.9 | | xsquared-2x= | | -20=4-6w | | 10a+_4a-3a= | | 4n-2-n=10 | | 15x-3=4x-14 | | (2x+4)=7 | | y-6=2(x-3) | | (2x^5)(4x^3)=x | | 9x-88=112+x | | 5(4+2x)-(8x-12)=69 | | -4a=2a+1-5a | | (2x+4)=76 | | 2v^2+2=196 | | 7x-7=x-4 | | 13+16x=18x-1 | | 2m+3m+9=29 | | 6x-122=58-3x | | 3gh-2g= | | k-4-6=16 | | 2x+7(3-y)i=-5+4i | | 2*(45-12y)+5y=174 | | -2.8-1.8= |